Some Contributions of the Institutional Investor Study - Jones, Lawrence D. (Journal of Finance, 1972)
Lawrence D. Jones, Some Contributions of the Institutional Investor Study, The Journal of Finance, Vol. 27, No. 2, Papers and Proceedings of the Thirtieth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 27-29, 1971 (May, 1972), pp. 305-317